Troisième Enquête Démographique et de Santé au Gabon (EDSG–III) 2019–21 - Direction Générale de la Statistique (DGS); The DHS Program (DGS et ICF, 2023)
Comprehensive survey results are published in the DHS Final Reports approximately 8-12 months after the completion of fieldwork. Standard reports are approximately 200 pages in length and include, but are not limited to, topics such as: household and respondent characteristics, fertility and family planning, maternal and child health, nutrition, and HIV/AIDS.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm